Interpolated retrieval effects on list isolation: Individual differences in working memory capacity. - Wahlheim, Christopher N.; Alexander, Timothy R.; Kane, Michael J. (Memory & Cognition, 2019)
We examined the effects of interpolated retrieval from long-term memory (LTM) and short-term memory (STM) on list isolation in dual-list free recall and whether individual differences in working memory capacity (WMC) moderated those effects. Ninety-seven subjects completed study–test trials that included two study lists separated by either an exemplar generation task (LTM retrieval) or a two-back task (STM retrieval). Subjects then completed an externalized free recall task that allowed for the examination of response accessibility and monitoring. Individual differences in WMC were assessed using three complex span tasks: operation span, reading span, and rotation span. Correct recall and intratrial intrusion summary scores showed no effect of interpolated retrieval on either response accessibility or monitoring. However, serial-position curves for correct recall of List 1 showed larger primacy in the two-back than in the exemplar generation task for high-WMC subjects. We interpreted these results from a context change perspective, as showing that interpolated LTM retrieval accelerated context change for subjects who processed the context more effectively. We consider the implications of these findings for models of memory.